2022
DOI: 10.3389/fmed.2021.745638
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Mediating Bradykinin-Induced Contraction in Murine and Human Detrusor Muscle

Abstract: Bradykinin (BK) has been proposed to modulate urinary bladder functions and implicated in the pathophysiology of detrusor overactivity. The present study aims to elucidate the signaling pathways of BK-induced detrusor muscle contraction, with the goal of better understanding the molecular regulation of micturition and identifying potential novel therapeutic targets of its disorders. Experiments have been carried out on bladders isolated from wild-type or genetically modified [smooth muscle-specific knockout (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…In addition to the connection to UTI, the genes and biological pathways affected by Gardnerella in our mouse model are related to bladder function and intersect with a wide range of other urological conditions, including but not limited to bladder cancer, urinary incontinence, bladder pain syndrome and interstitial cystitis. For example, cholinergic and bradykinin receptors and the neuropeptide neruotensin (Nts) mediate bladder muscle cell contraction ( Dong et al., 2015 ; Dalghi et al., 2020 ; Borsodi et al., 2021 ). Type 1 bradykinin receptors like Bdkrb1 are generally not expressed in healthy tissue but are induced by inflammatory mediators and injury ( Marceau et al., 1997 ), which is consistent with the increase in expression after Gardnerella exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the connection to UTI, the genes and biological pathways affected by Gardnerella in our mouse model are related to bladder function and intersect with a wide range of other urological conditions, including but not limited to bladder cancer, urinary incontinence, bladder pain syndrome and interstitial cystitis. For example, cholinergic and bradykinin receptors and the neuropeptide neruotensin (Nts) mediate bladder muscle cell contraction ( Dong et al., 2015 ; Dalghi et al., 2020 ; Borsodi et al., 2021 ). Type 1 bradykinin receptors like Bdkrb1 are generally not expressed in healthy tissue but are induced by inflammatory mediators and injury ( Marceau et al., 1997 ), which is consistent with the increase in expression after Gardnerella exposure.…”
Section: Discussionmentioning
confidence: 99%
“…CCG‐1423 (APExBIO) selectively inhibits SRF‐mediated transcription of Rho signalling pathway activation 21 . Y‐27632 (AbMole Bioscience) is a pharmacologically specific inhibitor of ROCK 22 . They were used to determine the regulatory role of RhoA/ROCK1 pathway in P. gingivalis infection cells.…”
Section: Methodsmentioning
confidence: 99%
“… 21 Y‐27632 (AbMole Bioscience) is a pharmacologically specific inhibitor of ROCK. 22 They were used to determine the regulatory role of RhoA/ROCK1 pathway in P. gingivalis infection cells. Control cells were those exposed to DMSO only.…”
Section: Methodsmentioning
confidence: 99%
“…Kinga Borsodi from Semmelweis University in Budapest, Hungary, showed that bladder contraction was mediated primarily via B2R [9]. In both human and murine bladders, contractions were independent of acetylcholine, ATP, or prostanoid mediators.…”
Section: Day 1 Of Conference: Kks Biologymentioning
confidence: 99%